THE ANALYSIS OF JUNIOR HIGH SCHOOL MATHEMATICS TEXTBOOK GRADE VII CURRICULUM 2013 - Yudita Rasma Aminati; Ali Mahmudi (Jurnal Pedagogi Matematika, 2017)
The  research  is  qualitative-quantitative  descriptive  that aimed  to  know  the  quality  ofmathematics  textbook  using  text  book   research  instrument  which  includes material,  presentation, language, and graph aspects. The object of this research is junior high school mathematics textbooksecond semester of grade VII curriculum 2013 revised edition in 2016 that be used in SMP Negeri 5 Yogyakarta. The data collection technique by using a questionnaire to kno the quality of matematicsh textbook that be used in SMP Negeri 5 Yogyakarta. Based on the result of analysis, can be concluded that junior high school mathematics textbook second semester of grade VII curriculum 2013 revised edition in 2016 that be used in SMP Negeri 5 Yogyakarta showed good criteria in material aspect with a percentage score is 75% and presentation aspect with a percentage score is 75%, sufficient criteria in language aspect with a percentage score is 50% and graph aspect with a percentage score is 56,25% according to Standar Penilaian Badan Peneliti dan Pengembangan Pusat Kurikulum dan Perbukuan.Keywords: analysis, mathematics textbook, matery, presentation, language, graph.